A Case of Pelvic Organ Prolapse and Bladder Diverticulum Surgically Treated at the Same Time - Yamamoto, Yasuyo (Hinyokika kiyo. Acta urologica Japonica, 2020)
We report a case of bladder diverticulum presumably caused by lower urinary tract dysfunction due to pelvic organ prolapse (POP) simultaneously treated with transurethral coagulation (TUC) of the bladder diverticulum and laparoscopic sacrocolpopexy (LSC). A literature search showed this is the first report of bladder diverticulum and POP surgically treated at the same time. A 71-year-old woman was referred to our hospital for the treatment of cystocele. She had both storage and voiding symptoms. She had a POPQ stage III cystocele and stage I uterine prolapse. Ultrasonography and computed tomographic scan showed a large volume of residual urine along with a bladder diverticulum. Since urodynamic studies revealed a low compliance bladder and obstruction, we opined that the lower urinary tract symptoms were induced by the cystocele. TUC of the bladder diverticulum and LSC were performed at the same time. After the operation, clean intermittent catheterization (CIC) was needed once a day for one month. Gradually, residual urine decreased and CIC became unnecessary. The bladder diverticulum disappeared, and there has been no recurrence of POP